2013
DOI: 10.4172/2155-6105.s4-009
|View full text |Cite
|
Sign up to set email alerts
|

Lower Left Thalamic Myo-Inositol Levels Associated with Greater Cognitive Impulsivity in Marijuana-Dependent Young Men: Preliminary Spectroscopic Evidence at 4T

Abstract: The effects of chronic marijuana (MRJ) use on neurochemistry are not well characterized. Previously, altered global myo-Inositol (mI) concentrations and distribution in white matter were associated with impulsivity and mood symptoms in young MRJ-dependent men. The objective of this study was to retrospectively examine previously collected data, to investigate the potential regional specificity of metabolite levels in brain regions densely packed with cannabinoid receptors. Spectra were acquired at 4.0 Tesla us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…The two studies that were eligible for this review reported no group differences in most neurometabolites among marijuana users and healthy control subjects (Mashhoon et al, 2011; Silveri et al, 2011), with the exception of alterations in myo-inositol. Notably, changes in the thalamus (Mashhoon et al, 2011) and globally (Silveri et al, 2011) were noted with lower myo-inositol (Mashhoon et al, 2013) and myo-inositol/creatine ratio (Silveri et al, 2011) in chronic marijuana users with respect to healthy volunteers. These limited findings indicate that marijuana use may result in decreased glial proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The two studies that were eligible for this review reported no group differences in most neurometabolites among marijuana users and healthy control subjects (Mashhoon et al, 2011; Silveri et al, 2011), with the exception of alterations in myo-inositol. Notably, changes in the thalamus (Mashhoon et al, 2011) and globally (Silveri et al, 2011) were noted with lower myo-inositol (Mashhoon et al, 2013) and myo-inositol/creatine ratio (Silveri et al, 2011) in chronic marijuana users with respect to healthy volunteers. These limited findings indicate that marijuana use may result in decreased glial proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with psychotic disorders suicidal behavior was associated with reduced GMV in cortical and subcortical structures including the left thalamus (Giakoumatos et al, 2013). In magnetic resonance spectroscopic imaging, marijuana users exhibited significantly reduced myo-Inositol levels in the left thalamus, relative to non-using participants, in association with elevated cognitive impulsivity as assessed by BIS-11 (Mashhoon et al, 2013). Reductions in myo-Inositol levels are suggestive of regional glial loss, which can lead to altered regional neurotransmission and GMV reduction (Gispert et al, 2016, Rajkowska and Miguel-Hidalgo, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Similar to the FG, the thalamus is also moderately distributed with CB1 receptors (Glass et al, 1997; Wong et al, 2010) and has also exhibited altered gray matter tissue density (Matochik et al, 2005) and neurometabolite levels (Silveri et al, 2011; Mashhoon et al, 2013) in MJ users. Chronic consumption of MJ, such as the patterns established by MJ users in the present study, and consequent regular binding of THC to CB1 receptors may directly alter the volume of the thalamus through a combination of axonal, neuronal and myelin loss (Evangelou et al, 2000; Hof et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampus, amygdala and thalamus, regions demonstrating high CB1 receptor distribution (Herkenham et al, 1991), also were selected for volumetric analysis based on evidence that MJ users exhibit functional and neurochemical alterations in these regions related to marijuana use (Ashtari et al, 2011; Bolla et al, 2005; Cousijn et al, 2012; Demirakca et al, 2011; Gilman et al, 2014; Glass et al, 1997; Hester et al, 2009; Mashhoon et al, 2013; Matochik et al, 2005; Schacht et al, 2012; Sneider et al, 2013; Sneider et al, 2014; Yucel et al, 2008). Clinical measures of mood and impulsivity were examined relative to cortical thickness and brain volume to further probe potential links with neurobiological consequences of marijuana use.…”
Section: Introductionmentioning
confidence: 99%